2021
DOI: 10.3390/cancers13184639
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in Treatment with Immune Checkpoint Inhibition and Targeted Therapy for Advanced Melanoma: A Nationwide Cohort Study

Abstract: Recent meta-analyses show conflicting data on sex-dependent benefit following systemic treatment for advanced melanoma patients. We examined the nationwide Dutch Melanoma Treatment Registry (July 2013–July 2018), assessing sex-dependent differences in advanced melanoma patients (stage IIIC/IV) with respect to clinical characteristics, mutational profiles, treatments initiated, grade 3–4 adverse events (AEs), treatment responses, and mortality. We included 3985 patients, 2363 men (59%) and showed that although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…In recent years, multiple meta-analyses have been published investigating the sex-dependent magnitude of benefit following treatment with immune checkpoint inhibition. The first study showed that men have more benefit from immune checkpoint inhibition, including anti-PD-1 [3], whereas the latter three showed no difference in efficacy and overall survival [4][5][6]. Our study supports the findings that sex on itself is not a predictor for response to anti-PD-1 treatment.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, multiple meta-analyses have been published investigating the sex-dependent magnitude of benefit following treatment with immune checkpoint inhibition. The first study showed that men have more benefit from immune checkpoint inhibition, including anti-PD-1 [3], whereas the latter three showed no difference in efficacy and overall survival [4][5][6]. Our study supports the findings that sex on itself is not a predictor for response to anti-PD-1 treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Sex differences in expression of ICs are important because they can lead to differences in responses to ICI treatment. Studies have reported differences in immunogenic missense mutation load, treatment response (durable clinical benefit), and survival between males and females in lung cancer [ 192 ] and melanoma [ 193 194 ]. In the case of CRC, there are lack of data on sex difference so far, and further studies on sex differences will be needed to predict treatment response as ICI treatment is expected to be activated in the future.…”
Section: Sex Differences In Pathogenesismentioning
confidence: 99%
“…These data were also confirmed in a separate cohort of 95 melanoma patients in which missense variants were 293 and 259 for male and female patients, respectively. As far as specific BRAF mutations concern, Van der Kooij and colleagues [ 34 ] analyzed 3985 patients with advanced melanoma: BRAF V600E mutation was more frequent in women (46% females versus 36% males) in all age groups analyzed; on the other hand, BRAF V600K mutation was prevalent in male patients (8% males versus 4% females) regardless of age. Lokhandwala et al [ 35 ] did not find a statistically significant association between specific BRAF mutations and gender, though they confirmed a higher incidence of BRAF V600K mutation in male patients.…”
Section: Braf Mutations As Key Players Of Genetic Instability In Mela...mentioning
confidence: 99%